Information literacy, higher education and lifelong learning: Definition and description - Abdul Aziz, Rafidah; Masrek, Mohamad Noorman; Mohd Saad, Mohd Sharif (Persatuan Pustakawan Malaysia, 2009)
Lifelong learning is the development of human potential through a continuously supportive process which stimulates and empowers individuals to acquire all the knowledge, values, skills, and understanding they will require throughout their lifetimes and to apply them with confidence, creativity and enjoyment in all roles, circumstances, and environments. Equally important is information literacy, which is referred to as the ability to locate, evaluate, manage, use and communicate information effectively for various purposes. This paper discusses the concept of lifelong learning, iriformation literacy and higher education. Today 's higher education requires students to be learners who create their own knowledge by interacting with i11formation from a variety of sources. This form of learning requires students to become effective users of information regardless of its format. They must learn skills for searching, retrieval, evaluation and use of the growing body of iriformation and knowledge. Higher education should be self-directed to inculcate independent learners who would be prepared to be lifelong learners.